Honey Analysis 2017
DOI: 10.5772/66330
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Maltese Honey

Abstract: The Maltese Islands are renowned for the production of genuine honey from diferent loral sources depending on the season and the location of the apiary. Honey samples were collected directly from local beekeepers over a period of 4 years. Each sample was coded and the details provided by the beekeepers were recorded. A total of 259 samples were collected. The distribution of the apiaries was also considered for the three honey seasons: spring, summer and autumn. All samples were tested for the parameters accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Another typical agricultural product, unique to the Maltese Islands is honey (Attard and Mizzi, 2013 ). Although honey is a sought-after product (Attard and Douglas, 2017 ), by-products of honey extraction and honey left over in hives for extended periods are not fit for direct human consumption and may be considered as a potential starting material for vinegar production. Hence, it can be diluted to obtain a brix content of 18% solution and fermented.…”
Section: Methodsmentioning
confidence: 99%
“…Another typical agricultural product, unique to the Maltese Islands is honey (Attard and Mizzi, 2013 ). Although honey is a sought-after product (Attard and Douglas, 2017 ), by-products of honey extraction and honey left over in hives for extended periods are not fit for direct human consumption and may be considered as a potential starting material for vinegar production. Hence, it can be diluted to obtain a brix content of 18% solution and fermented.…”
Section: Methodsmentioning
confidence: 99%
“…Published literature on Maltese honey is lacking, and up till now, no in-depth chemical profiling has been performed on Maltese honey; in fact, the literature is mainly based on physicochemical parameters. These studies include HMF content, diastase and proline levels, and total phenolic content [ 9 , 10 , 11 ]. More recently, a comprehensive study with regards to a number of physicochemical parameters and sugar composition has also been published [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies include HMF content, diastase and proline levels, and total phenolic content [ 9 , 10 , 11 ]. More recently, a comprehensive study with regards to a number of physicochemical parameters and sugar composition has also been published [ 11 ]. Furthermore, little or no comparison has been performed with regards to the physicochemical and chemical properties of Maltese honey with honey samples from other regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, numerous studies have demonstrated that principal component analysis (PCA), partial least squared-discriminant analysis (PLS-DA), and canonical discriminant analysis (CDA), among other techniques, allow for the discrimination of different honey types, determine the maturity of the honey, identification of adulteration, and for the confirmation of the presence of specific components [ 23 , 24 ]. A number of different studies have been carried out on the Maltese honey based on physicochemical parameters; these included HMF content, diastase and proline levels, total phenolic content, and sugar composition [ 25 , 26 ]. More recently, a comprehensive study based on the attenuated total reflection mid-infrared (ATR-FT-MIR) spectroscopy showed that it was possible to discriminate and classify local honey from that of non-local samples highlighting the authenticity of the Maltese honey [ 27 ].…”
Section: Introductionmentioning
confidence: 99%